Islamic Morals Improvement: Aqidah Akhlak Subject Teachers' Influence on Students: Peningkatan Akhlak Islami: Pengaruh Guru Mata Pelajaran Aqidah Akhlak terhadap Siswa - Wahyudi, Imam; Nadlif , Ainun (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative study investigates the crucial role of teachers in nurturing Islamic morals among students, focusing on MA Salahuddin Nangalili. Through observation, interviews, and documentation analysis, the study reveals the multifaceted roles of teachers as educators, community members, and learning managers. Results demonstrate that teachers effectively fulfill their duties and responsibilities, serving as guides and mentors in shaping students' moral development. The findings underscore the significance of integrating moral education into the structural process of educational development, emphasizing the bonded relationship between teachers and students in facilitating continuous learning and moral growth. This research contributes to understanding the dynamics of Islamic education and highlights the implications for fostering moral values within educational institutions. Highlights: Teachers as Moral Guides: Teachers play a pivotal role in shaping students' moral development through their guidance and mentorship. Integration of Moral Education: The study emphasizes the importance of integrating moral education into the structural process of educational development. Bonded Teacher-Student Relationship: The findings highlight the significance of the bonded relationship between teachers and students in facilitating continuous learning and moral growth. Keywords: Teacher's Role, Islamic Morals, Educational Integration